2019
DOI: 10.1021/acs.chemrestox.9b00350
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers Quinone Induces NCOA4-Mediated Ferritinophagy through Selectively Autophagic Degradation of Ferritin

Abstract: Polybrominated diphenyl ethers (PBDEs) have been detected ubiquitously in biological and environmental samples. Growing epidemiological data suggested the obvious correlation of PBDEs exposure with adverse health outcomes toward human beings, but exact molecular mechanism(s) are limited. Especially, the toxicological information regarding PBDEs metabolites is missing. Thereafter, this study intends to explore unidentified cell death modalities caused by PBDEs reactive quinone-type metabolite, PBDEQ. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…mRNA expression of NCOA4, which is a selective cargo receptor known to guide ferritin to the autolysosome, rapidly decreased after 2 h of hypoxia and reached significance after 4 h (Fig. 1L) [ 18 , 19 ]. The decrease of NCOA4 mRNA may suggest a link between ferritinophagy and hypoxia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA expression of NCOA4, which is a selective cargo receptor known to guide ferritin to the autolysosome, rapidly decreased after 2 h of hypoxia and reached significance after 4 h (Fig. 1L) [ 18 , 19 ]. The decrease of NCOA4 mRNA may suggest a link between ferritinophagy and hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Iron release from ferritins is regulated by a process known as ferritinophagy. Ferritinophagy is mediated by nuclear receptor coactivator 4 (NCOA4), which directly binds FTH and transfers the complex to the autolysosome for degradation [ [15] , [16] , [17] , [18] ]. NCOA4 has, in contrast to FTH, a low affinity to FTL indicating that ferritinophagy is predominantly regulated via the NCOA4-FTH system [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a fundamental difference in molecular mechanism between ferroptosis and other cell death, including apoptosis, necrosis and autophagy (Gao et al, 2016). Ferroptosis is morphologically manifest by smaller mitochondria with condensed membrane and reduced or vanished cristae (Dong et al, 2019;Park & Chung, 2019). Increasing evidences show that ferroptosis serves a crucial role in cancer cell death among various cancer types including CRC (Chen et al, 2020;Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their further peroxidase-oxidated products, quinones, may occur. Previously, our studies have demonstrated a highly reactive metabolite, PBDEs quinone (PBDEQ), exposure results in ROS production in cells, accompanied by autophagy, apoptosis, and DNA damage. , However, it is currently unknown whether PBDEQ causes pyroptosis or activates inflammasome. In the present study, we demonstrated the pyroptosis and NLRP3 inflammasome activation induced by PBDEQ in J774A.1 macrophages.…”
Section: Introductionmentioning
confidence: 99%